Case report: Pulmonary endarterectomy in Takayasu arteritis patient with group IV pulmonary hypertension: A rare clinical scenario - Unaldi, Erdinc; Firlatan, Busra; Duzgun, Selin Ardali; Koca, Suleyman Serdar; Yildizeli, Bedrettin; Akdogan, Ali (Wiley, 2024)
[Abstract Not Available]